1982
DOI: 10.1017/s0068246200009466
|View full text |Cite
|
Sign up to set email alerts
|

Sculptors from Aphrodisias: Some New Inscriptions

Abstract: SCULTORI DA AFRODISIADE: ALCUNE NUOVE ISCRIZIONITre nuove iscrizioni da Aphrodisias in Caria descrivono i cittadini locali — Flavius Zeno e Flavius Andronicus — come autori delle statue (ora perse) che stanno dedicando. Essi sono probabilmente il Flavius Zeno e il Flavius Andronicus di Aphrodisias le cui ‘firme’ — con l'asserzione che essi hanno ‘fatto’, ἐποίει, le statue — appaiono sui plinti di alcune statue trovate sull'Esquilino. II titolo da essi usato — sia ad Aphrodisias che a Roma — non può essere ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1988
1988
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…Epigraphic evidence suggests that sculptors from Aphrodisias were also famous abroad and worked on special commissions throughout the Roman Empire. Nearly 40 inscribed signatures have been found on sculptures in Italy, Greece, Crete and Asia Minor, as well as at Aphrodisias itself (Erim & Roueché, 1982: 102–115; Pensabene, 2002: 217–219).…”
Section: Historical Setting and Contribution Of The Research To Previ...mentioning
confidence: 99%
“…Epigraphic evidence suggests that sculptors from Aphrodisias were also famous abroad and worked on special commissions throughout the Roman Empire. Nearly 40 inscribed signatures have been found on sculptures in Italy, Greece, Crete and Asia Minor, as well as at Aphrodisias itself (Erim & Roueché, 1982: 102–115; Pensabene, 2002: 217–219).…”
Section: Historical Setting and Contribution Of The Research To Previ...mentioning
confidence: 99%
“…Fraser and Rönne (1957: 92-101) first argued that the lack of inclusion of an ethnic on funerary markers in Boeotia and Hellenistic Rhodes meant the individual was native to that area. Accordingly, it has been suggested that the absence of a toponym in the signature meant that the sculptor was local (Erim and Roueché 1982;Stewart 1990), even though local sculptors often did include a toponym. Furthermore, signatures, particularly of Hellenistic sculptors, seem not always to follow the expected patterns: Fraser (2009) has noted the peculiar use of the term Rhodios, rather than the more typical demotic (as used by Athenian sculptors while working in Athens), by sculptors at Rhodes, wondering if these craftsmen are foreign residents with limited citizenship rights for themselves and their descendents (for an alternative discussion of the possible meanings of Rhodios, see Goodlett 1991: 678-81).…”
Section: A Note On Toponymsmentioning
confidence: 99%
“… 74 IGUR IV.1592–1611, with Erim and Roueché 1982. On the statues: Bergmann 1999: 14–17; Moltesen 2000; Vorster 2012/2013: 396–400.…”
mentioning
confidence: 99%